Arteritis and Plexiform Lesion in Intralobar Pulmonary Sequestration: The First Case With Such Two Distinct Complex Lesions Associated With Local Pulmonary Hypertension. (May 2020) - Hashimoto, Hirotsugu; Matsumoto, Jun; Kusakabe, Masashi; Usui, Genki; Hiyama, Noriko; Yamaguchi, Hirokazu; Horiuchi, Hajime; Morikawa, Teppei
In intralobar pulmonary sequestrations, vascular changes similar to those in pulmonary hypertension (PH) are generally observed, such as intimal proliferation and plexiform lesions. However, to our knowledge, a sequestrated lung manifesting vascular changes with both arteritis and a plexiform lesion has never been reported. A 25-year-old man was diagnosed with intralobar pulmonary sequestration. Pathologically, both arteritis and a plexiform lesion were observed in the sequestrated lung. Systemic vasculitis syndrome was clinically excluded, and the pathological findings appeared to be associated with local PH. Arteritis is an extremely rare finding; only one case of arteritis associated with local PH has been reported in intralobar sequestration. In this case, the artery near the plexiform lesion had milder inflammation and fibrosis, suggesting that the arteritis formed prior to the plexiform lesion. This is the first case of arteritis and a plexiform lesion co-occurring in intralobar pulmonary sequestration associated with local PH. This case may shed light on the formation of plexiform lesions and their association with arteritis.